Exploring Gender and Sex Differences in Behavioral Dyscontrol: from Drug Addiction to Impulse Control Disorders - Liana Fattore (Frontiers Research Topics, 2016)
Males and females exhibit discrete attitudes and skills, experience dissimilar emotional and psychological needs, and react differently to peer pressure, lack of self-realization, or other personal and social expectations. In addition, they are differently influenced by family history, and diverge in the perception of self-image and health risks. To complicate the matter on gender dichotomy, male testosterone levels markedly vary over the course of the day, while female levels of sex hormones significantly fluctuate depending upon the menstrual cycle, the pre- or post-menopausal age, and the use of oral contraceptives. All of these factors interact with genetic background and sex hormonal fluctuations, and determine the differences observed in their predisposition to develop an addiction. This term is traditionally associated to the abuse of legal and illegal substances. However, a compulsion toward the engagement in a non-drug-related rewarding behavior, usually involving a natural reward, also activates the brain reward system and engenders persistent behavior, thus resulting in a diminished control over it. These latter behaviors are defined as "behavioral addictions". This definition encompasses any behavior characterized by the followings: i) feeling of tension or arousal before the action; ii) gratification and/or relief at the time of performing the act; iii) inability to resist an urge or drive even against great obstacles or dangers; iv) absence of consideration for the negative consequences that may affect family, friends, and/or work. As such, behavioral addictions include compulsive food intake and sexual activity, pathological gambling and Internet addiction, excessive exercising, compulsive buying and pyromania. These behaviors, which are often classified as "impulse control disorders", result in actions that are harmful to oneself and/or others, share common features (e.g. compulsiveness, impulsivity, impaired decision-making, craving, tolerance, withdrawal, high rates of relapse), and involve dysfunction of several brain circuits. Derangement from functional neurobiological mechanisms underpinning both sensitivity to reward and inhibitory control can also lead to compulsive behaviors. For instance, pathological gambling and other impulse control disorders (e.g., hypersexuality, compulsive painting, eating and buying) are often reported in Parkinson's disease patients. Gender-dependent differences in the rate of initiation and frequency of misuse of addicting drugs have been widely described. Yet, men and women also differ in their propensity to become addicted to other rewarding stimuli (e.g. sex, food) or activities (e.g. gambling, exercising). The goal of the present Research Topic is to explore and summarize current evidence for gender (and sex) differences not only in drug addiction, but also in other forms of addictive behaviors. Thus, it will include studies showing gender-dependent differences in drug addiction, food addiction, compulsive sexual activity, pathological gambling, Internet addiction and physical exercise addiction. Psychiatric comorbidity, potential risk factors and the underlying neural mechanisms will be also examined, with particular emphasis to the role of sex hormones in modulating addictive and compulsive behaviors.